Green Synthesis of AgNPs and Fe2O3NPs Using Garlic Plant and Study their Anticancer Activity against Cervical Cancer Cells - Ali, Hala H.; Mohammed Noori, Farah T. (Iraqi Journal of Physics, 2024)
In this study, silver and iron nanoparticles were biosynthesized using the garlic plant, an economical and environmentally friendly method. A blend of chitosan (CS) and polyvinylalcohol (PVA) was prepared. The silver nanoparticles (AgNPs), iron oxide nanoparticles (Fe2O3NPs), and the (CS/PVA) blend were characterized by X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), and Field Emission Scanning Electron Microscopy (FE-SEM) analyses. The FE-SEM images revealed that Fe2O3NPs were cubical and hexagonal, and AgNPs were spherical aggregates. AgNPs with blend (CS/PVA) and Fe2O3NPs with blend (CS/PVA) and (Fe2O3NPs/blend (CS/PVA) /AgNPs) composite were synthesized and tested for anticancer activity against cervical cancer cells (Hela) using the MTT assay. Best kills and the highest inhibitory effect were observed in (AgNPs/blend (CS/PVA)) and (Fe2O3NPs/Blend (CS/PVA)/AgNPs) composite. These findings demonstrated the method’s ability to synthesize nanocomposites with desirable physical, chemical and biological properties. Therefore, these findings demonstrate the new antibacterial and robust cytotoxicity features of the nanocomposite material, which has promising medical applications.